2007
DOI: 10.1785/0120050118
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Recurrence of Large Earthquakes on the Haiyuan Fault near Songshan, Gansu Province, China

Abstract: The Haiyuan fault is a major active left-lateral fault along the northeast edge of the Tibet-Qinghai Plateau. Studying this fault is important in understanding current deformation of the plateau and the mechanics of continental deformation in general. Previous studies have mostly focused on the slip rate of the fault. Paleoseismic investigations on the fault are sparse, and have been targeted mostly at the stretch of the fault that ruptured in the 1920 M ϳ8.6 earthquake in Ningxia Province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 59 publications
5
115
0
1
Order By: Relevance
“…Paleoseismological studies on the Haiyuan fault reveal that the average recurrence intervals between major earthquakes are in the range of 1000 to 2000 years [Zhang et al, 1988b[Zhang et al, , 2003Ran et al, 1997]. Liu et al [2007] report about 1000 year recurrence interval along the section of the Haiyuan fault, west of our studied area. Thus, for 1000 -2000 year recurrence and 88 year elapse time, the total slip will be strongly biased by inclusion of the most recent event.…”
Section: Inferences Of Fault Slip Ratesmentioning
confidence: 55%
See 1 more Smart Citation
“…Paleoseismological studies on the Haiyuan fault reveal that the average recurrence intervals between major earthquakes are in the range of 1000 to 2000 years [Zhang et al, 1988b[Zhang et al, , 2003Ran et al, 1997]. Liu et al [2007] report about 1000 year recurrence interval along the section of the Haiyuan fault, west of our studied area. Thus, for 1000 -2000 year recurrence and 88 year elapse time, the total slip will be strongly biased by inclusion of the most recent event.…”
Section: Inferences Of Fault Slip Ratesmentioning
confidence: 55%
“…[60] Along the neighboring fault, the Laohu Shan fault, Liu et al [2007] trenched the Songshan site and found two datable events with vertical displacement a few centimeters. Using 10 m as the characteristic displacement associated with the two paleoseismic events [Lasserre et al, 1999], they argued for 12 ± 4 mm/yr slip rate.…”
Section: Comparison With Gps Interferometric Aperture Radar and Palmentioning
confidence: 99%
“…The Qilian Shan range to the north has also been affected by several, equally large (M 8-8.3) historical earthquakes along its NEvergent fold-thrust belt in 1927 (Gaudemer et al 1995). Palaeoseismic trenching along the central portion of the fault reveals four major events in the last 3.5-4 ka, yielding an earthquake recurrence time of almost 1000 years (Liu-Zeng et al 2007). Burchfiel et al (1989Burchfiel et al ( , 1991 suggested that only 10.5-15.5 km offset had occurred along the Haiyuan Fault by matching geological markers across the fault.…”
Section: Haiyuan Faultmentioning
confidence: 99%
“…1) (Zhang et al, 1987). It connects to the 1920 rupture trace through a major left stepover known to have influenced the propagation of large historical earthquakes (Liu-Zeng et al, 2007). Geodetic investigations using InSAR suggest no significant slip deficit builds up along the creeping section on average over the [2003][2004][2005][2006][2007][2008][2009] period, as it slips at plate loading rate (5 1 mm=yr).…”
Section: Introductionmentioning
confidence: 99%